2023
DOI: 10.3390/agronomy13092365
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Joint-Stem Prediction for Agricultural Robots in Grasslands Using Multi-Task Learning

Jiahao Li,
Ronja Güldenring,
Lazaros Nalpantidis

Abstract: Autonomous weeding robots need to accurately detect the joint stem of grassland weeds in order to control those weeds in an effective and energy-efficient manner. In this work, keypoints on joint stems and bounding boxes around weeds in grasslands are detected jointly using multi-task learning. We compare a two-stage, heatmap-based architecture to a single-stage, regression-based architecture—both based on the popular YOLOv5 object detector. Our results show that introducing joint-stem detection as a second ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…When plants have a fairly small size, joint stem detection enables automatic weeding, as for example in the work of Lottes et al [18], [19] and Weyler et al [1]. In our previous work [20], we perform joint stem detection for Rumex plants. We found that even for the human annotator it was challenging to identify the precise joint stem position, especially in settings where plants have reached advanced growing states, their structure increases in complexity meaning the joint stems can not be clearly identified.…”
Section: B Phenotyping In Real-world Settingsmentioning
confidence: 99%
“…When plants have a fairly small size, joint stem detection enables automatic weeding, as for example in the work of Lottes et al [18], [19] and Weyler et al [1]. In our previous work [20], we perform joint stem detection for Rumex plants. We found that even for the human annotator it was challenging to identify the precise joint stem position, especially in settings where plants have reached advanced growing states, their structure increases in complexity meaning the joint stems can not be clearly identified.…”
Section: B Phenotyping In Real-world Settingsmentioning
confidence: 99%